Designing a Positive Psychological Intervention (PPI) Program for Persons Who Use Drugs (PWUDs) - Masanda, Argel B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This manuscript explored the integration of positive psychological science in the context of treatment and rehabilitation of persons who use drugs (PWUDs). Banking on the psychological needs of PWUDs based on the initial investigation conducted by Masanda et., al. (2022), this study endeavors to design a Positive Psychology Intervention (PPI) program that aims to harness the Character Strengths and Virtues (CSV) of the PWUDs as supplemental to their drug abuse treatment and rehabilitation. Guided by Positive Psychology, only the exclusive psychologically relevant data were included in creating the comprehensive psychological program. Specifically, the session activities of PPI are designed to enhance the following CSVs of the PWUDs: conformity, hope, self-acceptance, assertiveness, self-esteem, self-regulation, openness to change, motivation, personal strength, patience, happiness, and belongingness. The designed PPI is a 14-session program intended to be delivered once a week within three months. It was subjected to the scrutiny of three expert psychologists with decades of forensic psychological experience. Based on their judgments guided by the evaluation standards stipulated by Yarbrough et al. (2010), the designed PPI serves the psychological needs of the PWUDs in terms of their drug abuse treatment and rehabilitation, with its session activities deemed as realistic, prudent, diplomatic, and frugal. The program also shows and conveys technically adequate activities relative to drug addiction that merits good service. Finally, PPI also secures legal and ethical requirements with due regard for the welfare of the PWUDs and other stakeholders. Pertinent implications and recommendations germane to the designed program are provided.